Fenomena Mengabaikan Keadilan dalam Penegakan Hukum - Yohanes Suhardin (Fakultas Hukum Universitas Gadjah Mada, 2009)
Happening phenomenon in law enforcement at current Indonesia is while justice progressively most moves over. Justice tend is ignored in law enforcement, eventually justice is fundamental and realities of laws. Even frequent being said justice is its heart of law, therefore while in law enforcement justice be ignored, law becomes not wherewith. Justice institute as institute foremost and castled deep enforcement episodic law functions as institute of place law to be kidded, commercialized and even commercial it’s called with jurisdiction mafia. That jurisdiction mafia takes shelter at turns back rule of law. To rule of law, justice and utility is sacrified. Apparatus enforcer law just focussed on legal security aspect without tries to respond society justice charge that wants that deep law enforcement to be done by that progressive ala close to justice point in society. It visually of justice verdict those are assessed soft especially in impacted corruption matter negative to realize it national aim which is society which fairs and affluent.